1990
DOI: 10.1111/j.1467-8624.1990.tb03562.x
|View full text |Cite
|
Sign up to set email alerts
|

Very Early Language Deficits in Dyslexic Children

Abstract: At 2 1/2 years of age, children who later developed reading disabilities were deficient in the length, syntactic complexity, and pronunciation accuracy of their spoken language, but not in lexical or speech discrimination skills. As 3-year-olds, these children began to show deficits in receptive vocabulary and object-naming abilities, and as 5-year-olds they exhibited weaknesses in object-naming, phonemic awareness, and letter-sound knowledge that have characterized kindergartners who became poor readers in ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
384
5
17

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(443 citation statements)
references
References 53 publications
(58 reference statements)
34
384
5
17
Order By: Relevance
“…This relationship might also present in the opposite direction, with poor phonological skills impacting vocabulary development (Aguiar & Brady, 1991). Independent of the casual relation between phonological processing and vocabulary, research has demonstrated slow lexical development in children with DD (Lyytinen & Lyytinen, 2004; Scarborough, 1990). Alternatively, impaired SL might influence learning to read directly by reducing sensitivity to the statistical regularities that exist among letters and phonemes, including the discovery of phonological rules.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship might also present in the opposite direction, with poor phonological skills impacting vocabulary development (Aguiar & Brady, 1991). Independent of the casual relation between phonological processing and vocabulary, research has demonstrated slow lexical development in children with DD (Lyytinen & Lyytinen, 2004; Scarborough, 1990). Alternatively, impaired SL might influence learning to read directly by reducing sensitivity to the statistical regularities that exist among letters and phonemes, including the discovery of phonological rules.…”
Section: Discussionmentioning
confidence: 99%
“…Such a requirement is not entirely unexpected when the reciprocal relationship between phoneme awareness and reading skill is taken into account. The possibility that poor decoding skill is one manifestation of a broader and deeper linguistic problem should also be consid ered, because children who eventually experience difficulty in learning to read show deficits in pronunciation and object naming even before they encounter written language (Scarborough, 1990).…”
Section: Improving Decoding Skillsmentioning
confidence: 99%
“…Moreover, it is a neurobiological condition that reportedly affects approximately 80% of all individuals identifi ed as learning disabled (Bell et al, 2003;Shaywitz et al, 2007). Longitudinal studies, both prospective (Shaywitz et al, 1995;Francis et al, 1996) and retrospective (Scarborough, 1990;Bruck, 1992), indicate that dyslexia is a persistent, chronic condition; i.e. it does not represent a transient developmental delay as is the case with some other childhood disorders.…”
mentioning
confidence: 94%